2012
DOI: 10.1002/ptr.4836
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crocin on the Insulin Resistance and Lipid Profile of Streptozotocin‐Induced Diabetic Rats

Abstract: Crocin is the only water soluble carotenoid in nature, and it has a known powerful antioxidant activity. The aim of this work was to investigate the hypoglycemic and hypolipidemic effects of crocin in streptozotocin (STZ)-induced type 2 diabetic rats. Neonatal male Wistar rats (2-5 days old) were randomly divided into five groups. Three groups were intraperitoneally injected with STZ (90 mg/kg body weight). Among them, two groups were treated with intraperitoneal injection of crocin (50 or 100 mg/kg), and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
107
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 140 publications
(128 citation statements)
references
References 24 publications
19
107
0
2
Order By: Relevance
“…These results agreed with the present study in which crocin decreased significantly elevation of the serum lipid levels and increased the level of HDL in diabetic rats. Our findings also were comfirmed by Shirali et al (Shirali et al, 2013). They indicated that crocin decreased TG, total cholesterol and LDL and elevated HDL in diabetic rats by improving insulin resistance.…”
Section: Altinoz Et Al Afr J Tradit Complement Alternsupporting
confidence: 89%
“…These results agreed with the present study in which crocin decreased significantly elevation of the serum lipid levels and increased the level of HDL in diabetic rats. Our findings also were comfirmed by Shirali et al (Shirali et al, 2013). They indicated that crocin decreased TG, total cholesterol and LDL and elevated HDL in diabetic rats by improving insulin resistance.…”
Section: Altinoz Et Al Afr J Tradit Complement Alternsupporting
confidence: 89%
“…4,5 Crocin is the major active constituents of saffron which used in the traditional medicine for the treatment of numerous diseases including diabetes, depression, cognitive disorders and cancer. 6,7 Some investigations indicate that saffron and its constituents, crocin, have many pharmacological effects on diabetic animal models such as stimulation of glucose uptake by peripheral tissues, 8 inhibition of intestinal glucose absorption, 9 correction of insulin resistance, 10 stimulation and regeneration of beta cells in islets of langerhans to release more insulin. 11,12 As an interest, Hoshyaret al (2013) reported that Crocin triggers the apoptosis through increasing the Bax/Bcl-2 ratio and caspase activation in human gastric adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…A long-term increase in glucose is one of the most important causes of diabetes secondary disorders such as angiopathy, neuropathy, retinopathy, deficiency in the antioxidant defense system, and lipid profile disorders 2 . Hyperglycemia alone does not cause diabetic complications.…”
Section: Introductionmentioning
confidence: 99%